Signal propagation in conventional optical fiber and photonic crystal fiber in optical gyroscope - Хайдер Али, Аль-Судани (Radiotekhnika, 2017)
Photonic crystal fibers play a major role in the development of new fiber-laser sources of ultrashort light pulses and in creation of components of a fiber size to control these impulses. The fiber optic gyroscope is one of the applications of optical fibers, which depends mainly on the Sagnac effect. It belongs to the important areas of application, namely, to the domain of space navigation. Here it is proposed to use the photonic crystal fiber with a hollow core 1330nmλ, Ø10 mm in the optical gyroscope. Photonic crystal fibers exhibit the specific features and capabilities that lead to a huge potential for use in the field of measurement.